2008
DOI: 10.1152/ajpheart.00428.2008
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibition and gene deletion are protective against myocardial ischemia-reperfusion injury in vivo

Abstract: to dihydroxyeicosatrienoic acids. EETs are formed from arachidonic acid during myocardial ischemia and play a protective role against ischemic cell death. Deletion of sEH has been shown to be protective against myocardial ischemia in the isolated heart preparation. We tested the hypothesis that sEH inactivation by targeted gene deletion or pharmacological inhibition reduces infarct size (I) after regional myocardial ischemia-reperfusion injury in vivo. Male C57BL‫6گ‬J wildtype or sEH knockout mice were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 21 publications
7
88
0
Order By: Relevance
“…For example, CYP2J2 transgenic mice exhibited not only increased EET biosynthesis in coronary arteries, but also improved postischemic recovery of left ventricular function after myocardial I/R (Seubert et al, 2004). sEH inhibition through gene deletion or pharmacological suppression was protective against MIRI in mice (Motoki et al, 2008). Administration of exogenous 14,15-EET was found to reduce MIRI in rats and dogs (Nithipatikom et al, 2006; , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CYP2J2 transgenic mice exhibited not only increased EET biosynthesis in coronary arteries, but also improved postischemic recovery of left ventricular function after myocardial I/R (Seubert et al, 2004). sEH inhibition through gene deletion or pharmacological suppression was protective against MIRI in mice (Motoki et al, 2008). Administration of exogenous 14,15-EET was found to reduce MIRI in rats and dogs (Nithipatikom et al, 2006; , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although CYP2J2 and CYP2C both generate cardioprotective EETs from AA, studies have demonstrated that CYP2C also produces detrimental reactive oxygen species (ROS) (Fleming et al, 2001). In animal models, effective protection against MIRI has been shown by increasing EET concentrations through direct administration of EETs, upregulating the expression of AA epoxygenases using transgenic technology, or inhibiting the activity of sEH (Seubert et al, 2004;Motoki et al, 2008;Batchu et al, 2011;Oni-Orisan et al, 2014); decreasing 20-HETE generation through CYP4A/4F inhibition (Nithipatikom et al, 2004); and depressing ROS formation via CYP2C inhibition (Granville et al, 2004). AA-metabolizing P450 enzymes are thus considered to be therapeutic targets for MIRI and other CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, EETs and a soluble epoxide hydrolase inhibitor have been demonstrated to reduce infract size during I/R and improve cardiac function by preventing cardiac fibrosis (20,41,42). In contrast, cardiac overexpression of 12/15-LOX was reported to result in systolic dysfunction, inflammation, cardiac fibrosis, and macrophage infiltration (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased levels of 14,15-epoxyeicosatrienoic acid (14, in murine myocardium produced by either overexpression of the cytochrome P450 enzyme CYP2J3 or by genetic knock-out of soluble epoxide hydrolase resulted in decreased mPTP opening probability, improved preservation of mitochondrial membrane potential (⌬ mt ), and attenuated damage after ischemia/reperfusion (17,20,21). The diverse effects of prostaglandin E 2 (PGE 2 ), a cyclooxygenase-2 product, on cardiac function have been documented, which include the reduction of cardiac ischemia/reperfusion injury and a contribution to myocardial hypertrophy via prostaglandin E 2 receptor signaling (22,23).…”
mentioning
confidence: 99%
“…We used an established murine model of nonthrombotic acute MI, 21,22 with minor modifications. Male C57BL/6 mice (17-20 weeks) were intubated and ventilated under isoflurane anesthesia, the jugular vein was catheterized, and body temperature was maintained at 37°C.…”
Section: Myocardial Ischemia-reperfusion Injury Modelmentioning
confidence: 99%